2017
DOI: 10.1186/s12913-017-2331-z
|View full text |Cite|
|
Sign up to set email alerts
|

Costs of major intracranial, gastrointestinal and other bleeding events in patients with atrial fibrillation – a nationwide cohort study

Abstract: BackgroundUse of oral anticoagulation therapy in patients with atrial fibrillation (AF) involves a trade-off between a reduced risk of ischemic stroke and an increased risk of bleeding events. Different anticoagulation therapies have different safety profiles and data on the societal costs of both ischemic stroke and bleeding events are necessary for assessing the cost-effectiveness and budgetary impact of different treatment options. To our knowledge, no previous studies have estimated the societal costs of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 44 publications
2
24
1
Order By: Relevance
“…The attributable costs are the total costs of AF minus the total costs among the controls in accordance with previous publications [ 17 , 18 ]. Hence, attributable costs were estimated as a difference-in-difference in which the difference between costs for cases (AF patients) and controls was regarded as being attributable to the AF.…”
Section: Methodsmentioning
confidence: 92%
“…The attributable costs are the total costs of AF minus the total costs among the controls in accordance with previous publications [ 17 , 18 ]. Hence, attributable costs were estimated as a difference-in-difference in which the difference between costs for cases (AF patients) and controls was regarded as being attributable to the AF.…”
Section: Methodsmentioning
confidence: 92%
“…While the absolute risk is low, oral anticoagulants remain a common cause of bleedingrelated hospitalizations. [1][2][3][4][5] In one real-world study of patients with AF who were treated with oral factor Xa inhibitors, those who were hospitalized with a major bleed of any type were found to have mean hospital stays exceeding 5 days and inpatient mortality rates of approximately 3%, though mortality risk was notably higher for patients with intracranial hemorrhage (ICH) (approximately 14%). 4 There is a scarcity of nationally representative data describing the incidence and burden-of-illness of bleeding-related hospitalizations in AF patients, both overall and by bleed subtype.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Several prior studies have reported that the mean costs of ischemic stroke (IS) were significantly higher for patients with AF than for those without AF. 3 , 4 , 5 , 6 Two national database studies in Europe 7 , 8 estimated the mean costs for intracranial hemorrhage, gastrointestinal bleeding, and other major bleeding events in patients with AF. The acute care costs were 7331, 3601, 3941 Euros (EUR), and the average 3-year societal costs were 27,627, 17,868, and 12,384 EUR, respectively, suggesting that bleeding events also conferred a substantial economic burden on patients with AF.…”
Section: Introductionmentioning
confidence: 99%